2005
DOI: 10.1021/jp0520805
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Double-Proton Transfer in the 7-Azaindole Dimer in the Gas Phase. 3. Reaction Mechanism Studied by Picosecond Time-Resolved REMPI Spectroscopy

Abstract: The excited-state double-proton-transfer (ESDPT) reaction in the jet-cooled 7-azaindole dimer (7AI2) has been investigated with picosecond time-resolved resonance-enhanced multiphoton ionization spectroscopy. The observed decay profiles of 7AI2 by exciting the origin and the intermolecular stretch fundamental in the S1 state are well reproduced by single-exponential functions with time constants of 1.9 +/- 0.9 ps and 860 +/- 300 fs, respectively. This result provides clear evidence of the concerted mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
81
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 34 publications
2
81
0
Order By: Relevance
“…A support for this interpretation was given by Castleman and coworkers (20), who detected 7-azaindoleϩH ϩ mass-119 species after photoexcitation of the 7-azaindole dimer in the Coulomb explosion experiment. Recently, this interpretation of the gas-phase experiments was questioned by a series of works by Sakota and Sekiya and their coworkers (39)(40)(41)(42). They measured fluorescence excitation and hole-burning spectra of the jet-cooled 7-azaindole dimer in the S 1 -S 0 region and showed that the bandwidth of each vibronic band is largely different, depending on the vibrational mode (39).…”
Section: Mechanism Of the Double Proton Transfer Reaction Of The 7-azmentioning
confidence: 99%
“…A support for this interpretation was given by Castleman and coworkers (20), who detected 7-azaindoleϩH ϩ mass-119 species after photoexcitation of the 7-azaindole dimer in the Coulomb explosion experiment. Recently, this interpretation of the gas-phase experiments was questioned by a series of works by Sakota and Sekiya and their coworkers (39)(40)(41)(42). They measured fluorescence excitation and hole-burning spectra of the jet-cooled 7-azaindole dimer in the S 1 -S 0 region and showed that the bandwidth of each vibronic band is largely different, depending on the vibrational mode (39).…”
Section: Mechanism Of the Double Proton Transfer Reaction Of The 7-azmentioning
confidence: 99%
“…Very recently, we extensively studied the ESDPT reaction in 7AI 2 in the gas phase with frequency resolved and time-resolved spectroscopy. [42][43][44][45] In this paper, we provide final resolution of the stepwise versus concerted mechanism controversy regarding ESDPT in 7AI 2 . The discrepancies in the previous studies and important problems to be solved are summarized in Chaps.…”
mentioning
confidence: 97%
“…[18][19][20] The time scale of ESDPT in 7AI 2 ranges from subpicoseconds to picoseconds depending on the excitation energy of the UV light. 37,45 The appearance of strong fluorescence and a moderate time scale of the ESDPT reaction allow us to inves- …”
mentioning
confidence: 99%
See 2 more Smart Citations